2020
DOI: 10.1007/jhep07(2020)027
|View full text |Cite
|
Sign up to set email alerts
|

On taking the D → 4 limit of Gauss-Bonnet gravity: theory and solutions

Abstract: We comment on the recently introduced Gauss-Bonnet gravity in four dimensions. We argue that it does not make sense to consider this theory to be defined by a set of D → 4 solutions of the higher-dimensional Gauss-Bonnet gravity. We show that a well-defined D → 4 limit of Gauss-Bonnet Gravity is obtained generalizing a method employed by Mann and Ross to obtain a limit of the Einstein gravity in D = 2 dimensions. This is a scalar-tensor theory of the Horndeski type obtained by dimensional reduction methods. By… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
243
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(269 citation statements)
references
References 64 publications
14
243
2
Order By: Relevance
“…[24] using the ADM decomposition, and it was pointed out that the theory either breaks the diffeomorphism invariance or has additional degrees of freedom, thus in accordance with the Lovelock's theorem [20]. Nevertheless, the 4D-EGB theory can also be obtained as a particular case of the Horndeski theory [23]. In any case, the original solution proposed in [19] is also solution for the consistent formulations of the 4D-EGB theory [23,24].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…[24] using the ADM decomposition, and it was pointed out that the theory either breaks the diffeomorphism invariance or has additional degrees of freedom, thus in accordance with the Lovelock's theorem [20]. Nevertheless, the 4D-EGB theory can also be obtained as a particular case of the Horndeski theory [23]. In any case, the original solution proposed in [19] is also solution for the consistent formulations of the 4D-EGB theory [23,24].…”
Section: Introductionmentioning
confidence: 96%
“…However, a number of authors pointed out that this dimensional limit taking method is ill-defined [21][22][23]. For instance, divergent contributions to the field equations in four dimensions were observed [22], as well as the lack of covariant description [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are also some debates on whether the novel gravity is a consistent and well-defined theory in four dimensions [45][46][47][48][49][50][51][52][53]. Such as, Gurses et al pointed out that the novel 4D EGB gravity does not admit a description in terms of a covariantly-conserved rank-2 tensor in four dimensions and the dimensional regularization procedure is ill-defined, since one part of the GB tensor, the Lanczos-Bach tensor, always remains higher dimensional [46].…”
Section: Introductionmentioning
confidence: 99%
“…Based on studying the evolution of the homogeneous but anisotropic universe described by the Bianchi type I metric, Tian and Zhu found that the novel 4D EGB gravity with the dimensional-regularization approach is not a complete theory [49]. On the other hand, some regularized versions of 4D EGB gravity were also proposed by [51][52][53], and the resulting theories belong to the family of Horndeski gravity.…”
Section: Introductionmentioning
confidence: 99%